Pengaruh Komite Audit dan Kepemilikan Institusional terhadap Financial Distress - Siti Muthia Hanif Robbani; Ferdiansyah Ritonga (Program Studi Akuntansi Fakultas Ekonomi Universitas Samudra, 2024)
The aim of this research is to find out how institutional ownership and audit committees influence financial distress. Manufacturing companies in the industrial sector are the research population for the period 2018-2022. This research methodology uses a purposive sampling approach with a sample of 26 companies and a total of 130 financial reports. Multiple linear regression was used to analyze the data using the E-Views test. Based on research findings, institutional ownership has no effect on financial distress, but the audit committee has an effect on financial distress. The limitation of this research is the limited research sample because it was only carried out on industrial sector manufacturing companies listed on the Indonesia Stock Exchange (BEI) which was carried out for 5 years, namely from 2018-2022, then this research only used two variables, namely the audit committee and institutional ownership. . Suggestions for further research are expected to be able to add or expand the sectors studied or to add longer years of research. And it is hoped that further research will be able to measure financial distress using different models. Then, it is hoped that for companies it can be an illustration, especially for companies experiencing financial distress, to pay more attention to their finances.